2012
DOI: 10.1159/000337057
|View full text |Cite
|
Sign up to set email alerts
|

Ejaculatory Abstinence Influences Intravaginal Ejaculatory Latency Time: Results from a Prospective Randomized Trial

Abstract: Introduction: The relationship between ejaculatory frequency and ejaculatory latency time is under-investigated. Subjects and Methods: 120 healthy subjects were enrolled in a prospective randomized trial. Patients in group A engaged in sexual intercourse after a 10-day abstinence period for 3 months. Patients in group B engaged in sexual intercourse twice a week for 3 months. Ejaculation function was evaluated through the measurement of the intravaginal ejaculatory latency time (IELT) and through the premature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Palmieri et al . 7 demonstrated that a 10-day abstinence period led to a significantly lower mean IELT and a significantly higher mean total PEDT score than a twice-a-week abstinence in healthy people. They suggested that ejaculatory abstinence may influence the physiology of both male sexual organs (such as the prostate, seminal vesicles, and vas deferens) and the nervous system.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Palmieri et al . 7 demonstrated that a 10-day abstinence period led to a significantly lower mean IELT and a significantly higher mean total PEDT score than a twice-a-week abstinence in healthy people. They suggested that ejaculatory abstinence may influence the physiology of both male sexual organs (such as the prostate, seminal vesicles, and vas deferens) and the nervous system.…”
Section: Discussionmentioning
confidence: 92%
“… 4 5 6 Interestingly, a study showed that longer ejaculatory abstinence may lead to a shorter intravaginal ejaculatory latency time (IELT) in healthy people. 7 In addition, there is a postejaculation refractory time (PERT), or male refractory period (MRP), even after a single ejaculation in most human males, during which erection and ejaculation is inhibited. 8 Thus, we expect to determine if abstinence time, as well as immediately after ejaculation (abstinence time = 0), will interfere with the results of the SEPs and PSSR.…”
Section: Introductionmentioning
confidence: 99%
“…Although PE can be found in patients with organic diseases, in most cases psycho-relational factors are the main or unique determinants. 6,7 Evolutionary theories further support the concept of PE as a bother rather than a disease. For hominids, a faster ejaculation was a key factor to increase the chances of fertilization, thus preserving the genome.…”
Section: Discussionmentioning
confidence: 95%
“…For hominids, a faster ejaculation was a key factor to increase the chances of fertilization, thus preserving the genome. 7 When the human was in a stable relationship the frequency of sexual intercourse increased and the chances of fertilization improved. In the modern era, the control of ejaculation is perceived as an important feature of pleasure and couple's sexual health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation